Pomiar potencjału konkurencyjnego podmiotów konsolidujących się na przykładzie polskiego sektora bankowego - Marszałek, Jakub (Consolidating Companies Competitiveness Measurement - Polish Banking Sector Case, 2008)
Mergers and acquisitions are still one of the most common ways to execute company's development. Every decade has own M&A wave period although the economic profits of these transactions have not been proved undisputedly yet. Empirical research points to contradictory conclusions. There are many cases proving that mergers and acquisitions lead company to better financial or market standing. In the same time it is easy to point similar number of enterprises that lost after consolidation. How such paradox can be explained? How to justify this huge number of mergers and acquisitions executing all the time? There is no doubt that consolidation is one of the most complicated problems in the whole investment activity to analyze. Every enterprise can build its value by two sort of value drivers: measured in financial report and non-measured, calculated very generally, but necessary to evaluate the M&A transaction's profitability properly. Due to this problem there are several opinions claiming that consolidation cannot be economically assessed correctly because of insufficient measurement method's level. The aim of this paper is to suggest particular method of M&A's economical effects measurement. A new concept of company's competitiveness is formulated in the article. The empirical part of the paper presents an analysis of M&A transactions done by biggest Polish banks in the light of concept of competitiveness mentioned above.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 385-391